THE LEVEL AND QUALITY OF LIFE IN MODERN CONDITIONS (ULYANOVSK REGION AS AN EXAMPLE) - M. Rybkina; N. Ananeva; S. Smolenskaya (Вестник университета)
The article analyses the level and quality of life of the population of the Ulyanovsk region. The author shows demographic problems, the level of real monetary incomes and real wages. The article gives comparative analysis of the Ulyanovsk region with the Volga Federal District.